2019
DOI: 10.1063/1.5051765
|View full text |Cite
|
Sign up to set email alerts
|

A high pressure cell using metallic windows to investigate the structure of molecular solutions up to 600 MPa by small-angle neutron scattering

Abstract: We report on a high pressure (HP) cell designed for the determination of the structure of molecular solutions by small-angle neutron scattering (SANS). The HP cell is fitted up with two thick metallic windows that make the device very resistant under hydrostatic pressures up to 600 MPa (or 6 kbar). The metallic windows are removable, offering the possibility to adapt the HP cell to a given study with the pressure desired on an appropriate spatial range to study the structure of various molecular solutions by S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…HP-SANS experiments were performed using a new HP-SANS cell that we developed recently. 33 HP-SANS spectra were recorded for several tens of minutes at 5, 100, 150, 200, 250, and 300 MPa (the pressure change was made also at a rate of 10 MPa/min). Each BLG sample was also measured in a quartz Hellma ® cell (with a pathlength of 2 mm) before and after HP treatment.…”
Section: Eqmentioning
confidence: 99%
“…HP-SANS experiments were performed using a new HP-SANS cell that we developed recently. 33 HP-SANS spectra were recorded for several tens of minutes at 5, 100, 150, 200, 250, and 300 MPa (the pressure change was made also at a rate of 10 MPa/min). Each BLG sample was also measured in a quartz Hellma ® cell (with a pathlength of 2 mm) before and after HP treatment.…”
Section: Eqmentioning
confidence: 99%
“…The particle is chosen such that is does not adsorb on the test sample (here, a supramolecular polymer) and does sense its fluctuations (having a size larger than that of the test material). Typically, the MSD is measured by dynamic light scattering (DLS) techniques. , Different specialized sample cells for handling elevated pressures have been developed and utilized in neutron or X-ray scattering facilities or in conjunction with static or dynamic light scattering setups. , DLS-based microrheological LVE data were reported in the past, and very recently, a comprehensive study reported the design and implementation of a versatile experimental setup to obtain reliable data with fracturing fluids at pressures of up to 200 MPa . Both investigations , used passive microrheology based on diffusive wave spectroscopy (DWS).…”
Section: Introductionmentioning
confidence: 99%